Synthetic lincosamides iboxamycin and cresomycin are active against ocular multidrug-resistant methicillin-resistant Staphylococcus aureus carrying erm genes - Camille André; Kelvin J.Y. Wu; Andrew G. Myers; Paulo J.M. Bispo (Journal of Global Antimicrobial Resistance)
Objective: Antimicrobial resistance is a global pandemic that poses a major threat to vision health as ocular bacteria, especially methicillin-resistant Staphylococcus aureus (MRSA), are becoming increasingly resistant to first-line therapies. Here we evaluated the antimicrobial activity of new synthetic lincosamides in comparison to currently used antibiotics against clinical ocular MRSA isolates. Methods: Antimicrobial susceptibility testing was performed by broth microdilution for two novel synthetic lincosamides (iboxamycin and cresomycin) and eight comparator antibiotics against a collection of 50 genomically characterised ocular MRSA isolates, including isolates harbouring erm genes (n = 25). Results: Both drugs were active against widespread MRSA clonal complexes CC8 and CC5. The MIC50 and MIC90 of iboxamycin were 0.06 and 2 mg/L, respectively. Cresomycin (MIC50 = 0.06 mg/L) also displayed good activity with an in vitro potency four-fold higher (MIC90 = 0.5 mg/L) than iboxamycin. In isolates harbouring erm genes, MIC90 were >16, 2, and 0.5 mg/L for clindamycin, iboxamycin, and cresomycin, respectively. The in vitro potencies of iboxamycin and cresomycin were similar or higher than that of comparator agents and were not impacted by multidrug-resistance phenotypes or by the presence of erm genes when compared with clindamycin. Conclusions: Our results demonstrate that iboxamycin and cresomycin display potent in vitro activity against ocular MRSA isolates, including multidrug-resistant isolates harbouring erm genes.